Leadership Styles of School Heads in Public Secondary Schools Towards Educational Continuous Improvement Model - Mark Anthony T. Tangan (MultiTech Publisher, 2023)
This research study aimed to investigate the impact of various factors on leadership effectiveness and employee outcomes in educational settings. The study collected data through an adopted survey questionnaire from public secondary school heads in DepEd Cavite Province, analyzing the results to identify the leadership styles exhibited and to develop a model for educational continuous improvement. The findings revealed that age and educational attainment were significant factors in determining transformational leadership scores, while gender was not a significant predictor of leadership style preference for autocratic and democratic leadership styles. However, female participants scored higher under strategic leadership. Years of service did not have a significant impact on leadership effectiveness, except for participative leadership, which may be more compatible with younger employees. Certain leadership styles, such as democratic, transformational, and servant leadership, had a positive impact on employee engagement and job satisfaction. The study emphasized the importance of leaders adopting a flexible leadership approach that leverages the strengths of different leadership styles to achieve organizational goals. The findings suggest that organizations should invest in education and training programs to help leaders develop transformational leadership skills, promote diversity and inclusivity in their leadership teams, and prioritize promoting effective leadership styles to achieve positive employee outcomes. The proposed continuous improvement model should be used to maintain effective leadership practices and promote positive organizational outcomes. Further research is recommended to explore the relationship between leadership styles and organization’s achievement to develop a more comprehensive model for educational improveme